IMPLEMENTING REFORMS FOR MACROECONOMIC, LABOR PRODUCTIVITY GROWTH AND INVESTMENT IN UZBEKISTAN - Valieva Sayyora Khushbakovna; Uzokov Ma’murjon Shukhrat o’g’li (American Journals, 2022)
The essence of this issue is that the existing laws at the macroeconomic level, the problem and the decisions included in it, together with reforms aimed at reducing the number of unemployed in Uzbekistan, are an important role in investment and measures taken to increase the volume of investment.
Keywords: Reforms, Macroecomics, Labor, Finance, Policy, Investment